Urgensi Pendidikan Karakter Berbasis Pedagogik Profetik: Sebuah Pendekatan dalam Menanggulangi Krisis Moral Siswa - Yayu Asih Marlina; Yusuf Tri Herlambang; Tatang Muhtar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research aims to explore the urgency of character education oriented towards prophetic pedagogy in addressing students' moral crises. The discussion will delve into the concept of prophetic pedagogy, the values inherent within it, and how this approach can be implemented in the context of modern education. The research method employed in this study is a literature review method, which comprehensively elaborates on references from books, research journals, and other sources using Google Scholar and Garuda databases to enrich data and strengthen the discussion to remain relevant to the topic. The results of the research indicate that character education oriented towards prophetic pedagogy fundamentally aims to emphasize the understanding and practice of values such as honesty, compassion, and empathy. This form of character education can shape individuals with strong moral awareness and responsibility, capable of addressing moral decline by strengthening their moral foundation in accordance with religious teachings and spiritual traditions.